Challenges of Educational Philosophy (Humanism, Idealism, Naturalism, Pragmatism, Materialism, Existentialism) and its Impact on PAK in the Era of Globalization - Yeremia Jahtra Pay Phela; Nelson Hasibuan; Ampinia R. W. Rohy; Mario Alberto Manodohon (PT FORMOSA CENDEKIA GLOBAL, 2023)
Education in the current era of globalization is experiencing a value crisis. Education only produces outputs that are cognitively smart, master theory and technology but dry from human and social values ​​(dehumanization). The purpose of this article is to describe the challenges of educational philosophy and its impact on PAK in the era of globalization that philosophy is the view of life of a person or group of people which forms the basis for all aspects of their life. It must also be understood that in studying secular philosophy one must be careful. The Bible explains that, “Be careful that no one takes you captive with empty and false philosophies according to traditions and the spirits of the world, but not according to Christ (Col. 2:8). Educators must be thorough and examine each of these teachings with the truth of God's word (Prov. 16:2; 17:3; 21:2; Jer. 20:12; Gal. 6:4).